CRISPR-Cas12a based fluorescence assay for organophosphorus pesticides in agricultural products. (1st September 2022) - Fu, Ruijie; Wang, Yiwen; Liu, Yanlin; Liu, Haoran; Zhao, Qiyang; Zhang, Yaohai; Wang, Chengqiu; Li, Zhixia; Jiao, Bining; He, Yue
Highlights: A CRISPR-Cas12a-based method is developed for organophosphorus pesticides assay. MnO2 nanosheets are utilized as a bridge to connect the target-based recognition event with the activity of CRISPR-Cas12a. A two-enzyme cascade reaction strategy is designed to activate CRISPR-Cas12a. Good analytical performance toward paraoxon, dichlorvos and demeton is obtained. Abstract: Herein, we propose a sensitive fluorescent assay for organophosphorus pesticides (OPs) detection based on a novel strategy of activating the CRISPR-Cas12a system. Specifically, acetylcholinesterase (AChE) hydrolyzes acetylthiocholine into thiocholine (TCh). Subsequently, TCh induces the degradation of MnO2 nanosheets and generates sufficient Mn 2+ ions to activate the Mn 2+ -dependent DNAzyme. Then, as the catalytic product of activated DNAzyme, the short DNA strand activates the CRISPR-Cas12a system to cleave the fluorophore-quencher-labeled DNA reporter (FQ) probe effectively; thus, increasing the fluorescence intensity (FI) in the solution. However, in the presence of OPs, the activity of AChE is suppressed, resulting in a decrease in FI. Under optimized conditions, the limits of detection for paraoxon, dichlorvos, and demeton were 270, 406, and 218 pg/mL, respectively. Benefiting from the outstanding MnO2 nanosheets properties and three rounds of enzymatic signal amplification, the proposed fluorescence assay holds great potential for the detection of OPs in agricultural products.